2021
DOI: 10.1101/2021.12.10.472095
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A New Gene Set Identifies Senescent Cells and Predicts Senescence-Associated Pathways Across Tissues

Abstract: Although cellular senescence is increasingly recognized as driving multiple age-related co-morbidities through the senescence-associated secretory phenotype (SASP), in vivo senescent cell identification, particularly in bulk or single cell RNA-sequencing (scRNA-seq) data remains challenging. Here, we generated a novel gene set (SenMayo) and first validated its enrichment in bone biopsies from two aged human cohorts. SenMayo also identified senescent cells in aged murine brain tissue, demonstrating applicabilit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 101 publications
(180 reference statements)
0
4
0
Order By: Relevance
“…As senescence is a complex cellular response, which cannot be robustly represented by a single marker we examined the SenMayo senescence gene signature, a validated panel of 125 genes responsive to senescence in a range settings 26 . The SenMayo gene panel was significantly enhanced in LAM derived AT2 cells when compared with normal lung AT2 cells (Figure 3C and supplementary table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As senescence is a complex cellular response, which cannot be robustly represented by a single marker we examined the SenMayo senescence gene signature, a validated panel of 125 genes responsive to senescence in a range settings 26 . The SenMayo gene panel was significantly enhanced in LAM derived AT2 cells when compared with normal lung AT2 cells (Figure 3C and supplementary table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this idea, RNA sequencing showed increased activity in cytokine response pathways, consistent with SASP signalling and senescence in addition to injury as shown by increased apoptosis in lung parenchyma. scRNAseq data from LAM lungs showed that the SenMayo gene panel 26 , a set of 125 genes which identify senescent cells in multiple settings was increased in LAM when compared with control AT2 cells. Utilising scRNAseq from a patient treated with rapamycin, we observed that AT2 cell related senescent gene expression could be reduced by mTOR inhibitor therapy, reinforcing the role of mTOR dysregulation in LAM and AT2 cell senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytosis gene sets were curated from an extensive search of the literature, including papers by Park et al 74 , Lecoultre et al 75 and Janda et al 76 and extracted from the MGI gene ontology database. Senescence gene sets were extracted from papers by Eggert et al 32 , Kuilman et al 77 , özcan et al 78 , Acosta et al 79 , Fridman et al 80 , Coppé et al 81,82 , Buhl et al 83 and Saul et al 84 . LM22 and ImmuCC gene sets were derived from gene expression signatures published in Newman et al 85 and Chen et al 86 .…”
Section: Methodsmentioning
confidence: 99%
“…177 Importantly, senescent cells that accrue in aging tissues actively contribute to the inflammatory phenotypes. [180][181][182][183] A gene set containing numerous direct BMP/Wnt modulators (eg, Bmp2, Wnt2 [wingless2], Wnt16, Dkk1 [Dickkopf WNT signaling pathway inhibitor 1], etc) and targets of noncanonical Wnt action was shown to demarcate senescent cells in multiple tissues. 181 However, the conflicting literature on the role of Wnt agonists in promoting or preventing cell senescence suggests that canonical-noncanonical signaling bias and duration of signal exposure deserve additional investigation.…”
Section: Environmental and Modifiable Factors That Accelerate Calcifi...mentioning
confidence: 99%